Membangun Karakter Bangsa: Peran Pendidikan Pancasila dalam Pembentukan Etika Generasi Muda - Gumilar, Dinda Amelia; Lailufar, Hauna Fathiinah; Herawati, Nabila; Sofiyani, Navisa Elsofa; Salsyabella, Ratna Cahya; Hermayanti, Risa Aulia; Rahmadini, Rizqia; Furnamasari, Yayang Furi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The role of Pancasila education in shaping the ethics of the younger generation of students is becoming increasingly crucial to ensure that the nation's noble values are maintained and applied in everyday life. This study aims to determine the role of Pancasila education in shaping the younger generation. This research method specifically adopts a qualitative approach with a focus on analytical description. Data collection is carried out by collecting from various literature sources such as scientific journals, articles, books, and related expert works. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that civic education is essentially a conscious and planned effort to educate the nation's life for citizens by cultivating the nation's identity and morals as a basis for the implementation of the rights and obligations of defending the state for the survival of life and glory and the nation and state as well as the development of good citizen attitudes. Pancasila education as character education is one part of instilling character in students because in Pancasila education there is main character education and basic character education. Pancasila education in the Indonesian education curriculum is not only a symbol but also as an initial shield in facing the threat of the decline of the nation's noble values